Beyond business: Facebook’s role as a social institution against epistemic injustice - Venegas, Sarah Jane B. (Animo Repository, 2022)
A prevalent way of understanding Facebook, the biggest social media network, is by looking at it as a business. From its approach in many lawsuits against human rights, to its platform decisions, Facebook recognizes itself primarily as a business. While this is not inherently harmful, there are issues surrounding the platform that are better addressed using a different perspective. I believe one of these are epistemic injustices that happen in relation to Facebook. Epistemic injustices are moral wrongs done concerning people’s capacity to know. They occur when individuals are not able to fully exercise their epistemic rights because of unfair reasons. Epistemic injustice happens during attempts of communication – when one tries to acquire, share, or appreciate knowledge. These are scenarios Facebook is familiar with, having the goal of connecting people of diverse backgrounds. Leaving them unaddressed is detrimental to human dignity, epistemic development, and welfare of people in various aspects of life. With these, I argue that there is a need for Facebook to practice the virtue of epistemic justice as an institution. This is because Facebook is also a social institution, which can remedy epistemic injustices in ways that individual agents cannot. Institutions can do this through practicing structural virtues such as epistemic justice. Given this special ability, Facebook must do its part as an institution if we are to remedy epistemic injustice within the platform. The virtue of epistemic justice collectively refers to virtues that allow epistemic justice to be maintained and developed. By ‘practice’, the institution will act in accordance with the virtue in all senses of institutionalization (i.e., individual members, as a collective, and in its mechanisms/system). I show Facebook’s institutionalization using Miranda Fricker’s framework in defining social institutions in relation to epistemic virtues. In it she highlights the need for group agency, and the three different aspects that come with the institutionalization of a social group. Through my discussion, I also cite instances of epistemic injustice within the platform thus, showing that Facebook is unable to address the said injustices related to it. Then, I explain why Facebook need to practice the virtue of epistemic justice, using Elizabeth Anderson’s argumentation for structural virtues, especially epistemic justice. Finally, I end my paper by narrating ways Facebook may improve if the virtue is practiced.